A systematic review of scales for measuring information security culture. (4th December 2020) - Orehek, Špela; Petrič, Gregor
Abstract : Purpose: The concept of information security culture, which recently gained increased attention, aims to comprehensively grasp socio-cultural mechanisms that have an impact on organizational security. Different measurement instruments have been developed to measure and assess information security culture using survey-based tools. However, the content, breadth and face validity of these scales vary greatly. This study aims to identify and provide an overview of the scales that are used to measure information security culture and to evaluate the rigor of reported scale development and validation procedures. Design/methodology/approach: Papers that introduce a new or adapt an existing scale of information security culture were systematically reviewed to evaluate scales of information security culture. A standard search strategy was applied to identify 19 relevant scales, which were evaluated based on the framework of 16 criteria pertaining to the rigor of reported operationalization and the reported validity and reliability of the identified scales. Findings: The results show that the rigor with which scales of information security culture are validated varies greatly and that none of the scales meet all the evaluation criteria. Moreover, most of the studies provide somewhat limited evidence of the validation of scales, indicating room for further improvement. Particularly, critical issues seem to be the lack of evidence regarding discriminant and criterion validity and incomplete documentation of the operationalization process. Research limitations/implications: Researchers focusing on the human factor in information security need to reach a certain level of agreement on the essential elements of the concept of information security culture. Future studies need to build on existing scales, address their limitations and gain further evidence regarding the validity of scales of information security culture. Further research should also investigate the quality of definitions and make expert assessments of the content fit between concepts and items. Practical implications: Organizations that aim to assess the level of information security culture among employees can use the results of this systematic review to support the selection of an adequate measurement scale. However, caution is needed for scales that provide limited evidence of validation. Originality/value: This is the first study that offers a critical evaluation of existing scales of information security culture. The results have decision-making value for researchers who intend to conduct survey-based examinations of information security culture.